THE EXPERIENCE OF PURSUING A MASTER’S DEGREEIN THE PEOPLE’S REPUBLIC OF CHINA - V.A. Sekurova (Многоязычие в образовательном пространстве)
Education is one of the key factors influencing a person’s worldview. The article focuses on the specificity, the problems and opportunities of researching for a Master’s degree in China. The author shares her personal experience. The purpose of the study is to summarise and analyse the characteristics of education in China. The relevance of the work lies in the fact that in the context of the development of globalisation and internationalisation in world markets, students, receiving a Bachelor’s degree in their country, strive to increase their competitiveness through international ed-ucational experience. The PRC, thanks to its Master’s degree programmes, involves highly qualified international specialists into China’s educational service sector, developing a “soft power” approach to education, and increasing the international competitiveness of its country’s education. The conclusion is made that the majority of foreign students are satisfied with the results of their studies in China and have a positive opinion of the country of study, which they then retransmit in their sur-roundings. China successfully manages to form the image of a “mightiest cultural power,” the coun-try involves students into its socio-cultural environment, increases the influence of Chinese culture in order to strengthen its influence on foreign public opinion around the world.